Serum lactate dehydrogenase as a biochemical marker for maternal outcome in pre-eclampsia - Kumari, Gitanjali; Taralekar, Vaishali; Dabhadakr, Suchita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: LDH is a cytoplasmic intracellular enzyme present in the heart, kidney, muscle, leukocytes and erythrocytes, of all major organ systems. The presence of LDH in extracellular space points towards cellular damage, endothelial dysfunction. Preeclampsia is a multisystem disorder during pregnancy causing cellular damage or death. Hence, serum LDH levels can be helpful in determining the extent of cell damage and the seriousness of this disease. The present study aimed to correlate the maternal serum lactate dehydrogenase levels with maternal and perinatal outcomes in women with pre-eclampsia. Methods: It was a prospective observational study. A total of 120 antenatal patients diagnosed with hypertensive disorder of pregnancy were included in this study. Serum LDH levels were estimated by enzymatic method on the autoanalyzer. Patients were grouped into 3 categories according to serum LDH levels: a) <600 IU/l, b) 600-800 IU/l c) >800 IU/l. Clinical manifestation of development of complications of hypertensive disease and its relation with serum LDH in respective patients were analyzed. Results: An LDH level of more than 800 IU/l was seen in 19.2% while between 600 to 800 IU/l was seen in 16.7% cases. A significant association was observed between incidence of maternal complications with high LDH levels (p<0.01). High LDH levels were observed to be associated with development of ante-partum haemorrhage, eclampsia and requirement of ICU admission. No significant association was found between different categories of LDH and deep tendon reflexes, levels of proteinuria at the time of admission in these preeclamptic women. Conclusions: Close monitoring and early intervention of the preeclampsia patients with elevated serum LDH levels can help avoid adverse effects of the disease and thereby help improve maternal and perinatal outcomes in pregnant women with preeclampsia.